2018
DOI: 10.16930/2237-7662/rccc.v17n52.2727
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da gestão familiar na avaliação do desempenho da empresa: evidências do Brasil

Abstract: Esta pesquisa tem como objetivo verificar o efeito da gestão familiar na avaliação do desempenho de empresas brasileiras de capital aberto pertencentes ao setor de consumo cíclico listadas na Brasil, Bolsa, Balcão (B3). Para tanto, realizou-se uma pesquisa descritiva, documental e com abordagem quantitativa por meio da utilização da Regressão Linear Múltipla. O período de análise compreendeu os anos de 2012 a 2016. A amostra do estudo foi constituída por 34 empresas brasileiras familiares e 66 empresas não fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Nesse sentido, Atkinson et al (2008) e Maheshwari e Maheshwari (2021) apontam que a contabilidade gerencial é uma ferramenta capaz de maximizar os resultados por meio de informações que auxiliam no processo decisório e que, consequentemente, pode gerar melhorias no desempenho organizacional. No que diz respeito às empresas familiares, de acordo com Brandt et al (2018), a característica dessas empresas pode afetar o desempenho, visto que o conselho da maioria delas é formado por membros da família. Assim, indiretamente, essa configuração, ligada à informalidade dos processos gerenciais, afeta o desempenho das empresas familiares, como é o caso das empresas hoteleiras investigadas neste estudo.…”
Section: Contabilidade Gerencialunclassified
“…Nesse sentido, Atkinson et al (2008) e Maheshwari e Maheshwari (2021) apontam que a contabilidade gerencial é uma ferramenta capaz de maximizar os resultados por meio de informações que auxiliam no processo decisório e que, consequentemente, pode gerar melhorias no desempenho organizacional. No que diz respeito às empresas familiares, de acordo com Brandt et al (2018), a característica dessas empresas pode afetar o desempenho, visto que o conselho da maioria delas é formado por membros da família. Assim, indiretamente, essa configuração, ligada à informalidade dos processos gerenciais, afeta o desempenho das empresas familiares, como é o caso das empresas hoteleiras investigadas neste estudo.…”
Section: Contabilidade Gerencialunclassified
“…Moreover, Poutziouris et al (2015) 2017) realized that family businesses outperformed non-family firms, mostly due to the presence of the company's founder. When studying Brazilian firms, Brandt et al (2018) found that family ownership was positively related to ROA, arguing that an increase in family ownership can trigger an increase in performance, which indicates that the family has greater motivation to maximize business performance because their wealth is tied to it. However, the authors found that this variable do not significantly impact return on equity (ROE) and Tobin's Q.…”
Section: Family Structure and Performancementioning
confidence: 99%
“…Specifically, there are ten Brazilian family companies in the top 500 (Robertsson et al, 2021). Some researchers approached the performance of family firms in Brazil, such as Caixe and Krauter (2013), with data from 2001 to 2010; Degenhart et al (2016), who analyzed 32 family firms of the cyclical consumption sector from 2008 to 2012; Goes et al (2017), who used data only from 2013; Brandt et al (2018), who also studied firms of the cyclical consumption sector, but from 2012 to 2016; Lunardi et al (2020), who analyzed the performance of firms during the 2012 crisis; and Almeida and Flach (2020), who studied firms listed on the Brazil 100 Index (IBrX100) from 2012 to 2016.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, despite an extensive screening of multiple databases to identify papers that have discussed the antecedents of FB performance, there is little evidence regarding Brazilian FBs (Beuren, Politelo, & Martins, 2016;Brandt, Kroenke, & Pletsch, 2018;Wagner et al, 2015). For instance, Brazilian FBs have a higher sense of tradition and heritage than Anglo-Saxon FBs (Frezatti, Bido, Mucci, & Beck, 2017;Gupta & Levenburg, 2010) and face particular governance challenges that might affect their performance (Instituto Brasileiro de Governança Corporativa [IBGC], 2019).…”
Section: Open Accessmentioning
confidence: 99%